2020
DOI: 10.1126/sciadv.aaz1842
|View full text |Cite
|
Sign up to set email alerts
|

Giant isotope effect on phonon dispersion and thermal conductivity in methylammonium lead iodide

Abstract: Lead halide perovskites are strong candidates for high-performance low-cost photovoltaics, light emission, and detection applications. A hot-phonon bottleneck effect significantly extends the cooling time of hot charge carriers, which thermalize through carrier–optic phonon scattering, followed by optic phonon decay to acoustic phonons and finally thermal conduction. To understand these processes, we adjust the lattice dynamics independently of electronics by changing isotopes. We show that doubling the mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 42 publications
3
46
0
2
Order By: Relevance
“…The most-recent research on MAPbI 3 further addresses the isotope effect revealed earlier by Kong et al [ 77 ]. Manley et al [ 109 ] have extended their previous INS-TAS experiments on a per-deuterated MAPbI 3 [ 110 , 113 ] (see Figure 4 a), revealing that isotope substitution in MA + causes a large (20–50%) softening of the longitudinal acoustic (LA) phonons near zone boundaries, reduces thermal conductivity by nearly 50%, and slows carrier relaxation kinetics. These significant effects serve to emphasize once more out the importance of a coupling of LA phonons to the librational modes of the methylammonium molecule, which are strongly mass-dependent [ 109 ].…”
Section: Soft Media For Photovoltaics and Photonicsmentioning
confidence: 95%
See 4 more Smart Citations
“…The most-recent research on MAPbI 3 further addresses the isotope effect revealed earlier by Kong et al [ 77 ]. Manley et al [ 109 ] have extended their previous INS-TAS experiments on a per-deuterated MAPbI 3 [ 110 , 113 ] (see Figure 4 a), revealing that isotope substitution in MA + causes a large (20–50%) softening of the longitudinal acoustic (LA) phonons near zone boundaries, reduces thermal conductivity by nearly 50%, and slows carrier relaxation kinetics. These significant effects serve to emphasize once more out the importance of a coupling of LA phonons to the librational modes of the methylammonium molecule, which are strongly mass-dependent [ 109 ].…”
Section: Soft Media For Photovoltaics and Photonicsmentioning
confidence: 95%
“…A number of neutron scattering instruments have been used so far for the study of OHPs. These instruments can be roughly classified as triple-axis spectrometers (TAS), operating at reactor sources (e.g., HB3, HFIR, ORNL, US [ 109 ]; BT4 and SPINS at NIST [ 110 , 111 , 112 ], US; IN12 and IN22 at ILL, FR. [ 112 , 113 ]; 4F1, 4F2 and 1T at LLB, FR [ 113 , 114 , 115 , 116 ]); and the time-of-flight (TOF) instruments available at spallation (e.g., MAPS and MARI at ISIS, UK [ 117 , 118 , 119 ]; 4SEASONS and AMATERAS at J-PARC, JP [ 120 , 121 ]; or ARCS at SNS, ORNL, US [ 120 ]) and reactor sources (IN4 and IN5 at ILL, FR [ 116 , 117 , 122 ]).…”
Section: Soft Media For Photovoltaics and Photonicsmentioning
confidence: 99%
See 3 more Smart Citations